2023
DOI: 10.1371/journal.pone.0284696
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with depression, anxiety and stress symptoms among construction workers in Nepal

Bikram Adhikari,
Lisasha Poudel,
Niroj Bhandari
et al.

Abstract: Introduction The construction industry in Nepal, which employs a significant proportion of the population, ranks as one of the largest industries in the country. Construction work is physically demanding and can be risky due to the use of heavy machinery and the presence of intense physical labor. However, the physical and mental health of construction workers in Nepal is often neglected. This study aimed to assess psychological distress (depression, anxiety, and stress symptoms) and its association with socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Studies using self-report screening tools tended to show a higher prevalence of psychopathology in the context of construction. At the lowest end of the range, a regional study of 402 Nepalese construction workers measured a 17% prevalence of depressive symptoms [ 33 ]. At the highest end, a national study of 430 Korean field workers measured a 38% prevalence of depressive symptoms [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using self-report screening tools tended to show a higher prevalence of psychopathology in the context of construction. At the lowest end of the range, a regional study of 402 Nepalese construction workers measured a 17% prevalence of depressive symptoms [ 33 ]. At the highest end, a national study of 430 Korean field workers measured a 38% prevalence of depressive symptoms [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to depression, the documents included in this review also found a high prevalence of anxiety symptoms in construction populations in different parts of the world. A regional Nepalese study of workers on building construction sites measured a 19.2% prevalence of anxiety [ 33 ]. In construction participants living in China, moderate to extremely severe anxiety was measured at a prevalence of 33.6% [ 9 ]; in Australia, mild/moderate to severe anxiety was measured at a prevalence of 36% [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria for the articles were those focused on diversity in the CS and those related to construction workers and professionals. The irrelevant records were those that did not focus on diversity [37], articles belonging to other disciplines like medicine [38] or the electrical industry [39], and those articles that do not relate to construction workers or professionals [40].…”
Section: Data Retrievalmentioning
confidence: 99%
“…Stress, anxiety, and depression are important markers that can affect the brain, behavior, and cognition, and stress and depression have been linked to the occurrence of accidents [17,113,114]. Worker stress levels have been shown to have a negative impact on safety behavior [115][116][117], and it has been argued that reductions in occupational stress can improve safety compliance. Alonso et al [117] reported a high prevalence of job stress and emotional exhaustion symptoms.…”
Section: Relationship Between Stress Depression and Traumatic Eventsmentioning
confidence: 99%